Voting rules and endogenous trading institutions: An experimental study - Morten Søberg (Statistics Norway, Research Department, 2002)
This paper reports on recurring laboratory elections in which buyers and sellers choose institutional rules to govern a subsequent trading round. The bid auction (buyers propose prices), offer auction (sellers suggest prices) and double auction (both trader types initiate price quotes) make up the electoral candidates. Both plurality rule and approval voting are used as vote-counting schemes. The former allows each trader to vote for, at most, one auction, whereas approval voting permits voters to either abstain or to vote for one, two or all three institutional alternatives. The main result is threefold. First, plurality rule induces a Duverger effect in the sense that only the bid and offer auctions emerge as viable auctions. Approval voting instead leads to close three-way races with each of the three auctions winning approximately one third of the elections. Second, buyers (sellers) in the plurality-rule sessions concordantly vote for the bid (offer) auction. Approval-voting behavior is comparatively more heterogeneous. Third, bid-auction prices are significantly lower than double-auction prices, which again are significantly below offer-auction prices.
Keywords: D70; D44; C92; 330; Plurality rule; approval voting; sequential auctions; experimental economics.